Non-Refoulement Through Local Wisdom: Indonesia’s International Legal Compliance as a Non-Ratifying State in Handling Rohingya Refugees in Aceh - Roesa, Nellyana; Rosmawati, Rosmawati; Listriani , Sophia; Zaidi Daud , Mohd; Mahfud, Mahfud (Faculty of Law, Universitas Jambi, 2026)
Abstract Background: The legal issue of handling Rohingya refugees in Indonesia arises from the gap between the official state policy of rejecting the presence of Rohingya refugees, citing their non-ratification of the convention, and Aceh's social empathy for Rohingya refugees. Aceh's social acceptance and concern for Rohingya refugees stem from Acehnese local wisdom known as